We want to solve the following equation:
![2(6d+3)=18-3(16-3d)](https://img.qammunity.org/2023/formulas/mathematics/college/s8l7iy2m2s96z75wli1rq7mwej1ou4ouf5.png)
First, let's expand the parenthesis by using the distributive property.
![\begin{gathered} 2(6d+3)=18-3(16-3d) \\ 12d+6=18-48+9d \\ 12d+6=-30+9d \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/m1fz2poauswmjdv1n6ayxwhremsigjj2lo.png)
Now, let's subtract 6 from both sides of the equation.
![\begin{gathered} 12d+6-6=-30+9d-6 \\ 12d=-36+9d \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1jwiqp8vux9jf6hwn5ngx4nefllagilp4c.png)
Now, let's subtract 9d from both sides.
![\begin{gathered} 12d-9d=-36+9d-9d \\ 3d=-36 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qeo6v3l278qtg0i6l61pra0qgu7brms4fm.png)
And finally. let's divide both sides by 3.
![\begin{gathered} (3d)/(3)=-(36)/(3) \\ d=-12 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1bwpvbmju5ekzh8d6fe1psn8bd03ohkakn.png)
d = -12.